A Zebra Among Horses: A Case of Brugada Syndrome and Coronary Artery Disease. (April 2016) - Martin, Kyle L.; Hicks, Rodney W.
Abstract : Brugada syndrome (BrS) is recognized as a hereditary ion channel disorder with electrocardiographic changes. First appearing in the literature about 20 years ago, contemporary thoughts are that BrS may be responsible for many sudden cardiac deaths and is associated with ventricular dysrhythmias that can lead to syncope or cardiac arrest. Many individuals with BrS may have no or limited structural heart disease, whereas others may have subtle morphological changes in histopathology. This case reviews a single patient with BrS Type 1 who was found to have a high-level of coronary artery disease. Changes noted in the original electrocardiogram were of significant importance in reaching the diagnosis.